2020
DOI: 10.3390/nu12082197
|View full text |Cite
|
Sign up to set email alerts
|

The Role of a Food Literacy Intervention in Promoting Food Security and Food Literacy—OzHarvest’s NEST Program

Abstract: Food literacy interventions are widely implemented to improve the food security and health of low-socioeconomic adults. The purpose of this study was to conduct an inquiry into the value of OzHarvest’s six-week NEST (Nutrition Education and Skills Training) program in promoting food security and food literacy, and to identify the barriers and enablers that participants experienced in sustaining food security, and in utilising their food literacy skills beyond the program. A descriptive evaluation study with pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 67 publications
1
55
1
2
Order By: Relevance
“…Studies have indicated that FL can be modified to improve health, because people with higher FL can make better food choices than those with limited FL. 17 For example, among patients with heart failure, those who have higher levels of FL have lower sodium consumption, improved control of their disease, and higher quality of life. 18 The qualitative study by Karin et al reported FL as a facilitator of adherence to dietary guidance and demonstrated a link to increased fruit and vegetable consumption in renal transplant recipients.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated that FL can be modified to improve health, because people with higher FL can make better food choices than those with limited FL. 17 For example, among patients with heart failure, those who have higher levels of FL have lower sodium consumption, improved control of their disease, and higher quality of life. 18 The qualitative study by Karin et al reported FL as a facilitator of adherence to dietary guidance and demonstrated a link to increased fruit and vegetable consumption in renal transplant recipients.…”
Section: Introductionmentioning
confidence: 99%
“…Research on health literacy is slowly ongoing in Korea, but there has been little focus on nutritional and food literacy [ 22 ]. However, outside of Korea, the use of the concept of “food literacy” has significantly increased in research [ 23 ]. Moreover, the results of various interventions have been implemented widely over the past decade.…”
Section: Discussionmentioning
confidence: 99%
“…A high level of nutrition and food literacy determines beneficial dietary choices and may play an important role in the prevention of socially significant diseases [32]. Low levels of nutrition and food literacy may be related to purchasing unhealthy foods and succumbing to commercial marketing, which includes food advertising [33].…”
Section: The Significance Of Nutrition and Food Literacymentioning
confidence: 99%